2014
DOI: 10.1016/j.jclepro.2013.09.050
|View full text |Cite
|
Sign up to set email alerts
|

The link between eco-innovation and business performance: a Taiwanese industry context

Abstract: In practice, there are various types of eco-innovation. While each type of innovation has its own attributes, determinants, and contribution to business performance, it is not effective to implement eco-innovation programs without a holistic view. This study draws from the resource-based view theory to investigate inter-relationships among three types of eco-innovation (process, product, organizational) and their relative impact on business performance. Using structural equation modeling with 121 samples colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
420
2
31

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 470 publications
(487 citation statements)
references
References 81 publications
(71 reference statements)
34
420
2
31
Order By: Relevance
“…TCE suggests that a detailed contract can minimize any uncertainty associated with business transactions [24]. A higher degree of contract specificity could impose stronger control on business relationships and, thus, discourages opportunistic behavior or abuse [8,33]. Many studies suggested incorporating incentives into the contract (e.g., revenue sharing) to facilitate the implementation of joint sustainability initiatives [12,37].…”
Section: Effects Of Contractual Governancementioning
confidence: 99%
See 2 more Smart Citations
“…TCE suggests that a detailed contract can minimize any uncertainty associated with business transactions [24]. A higher degree of contract specificity could impose stronger control on business relationships and, thus, discourages opportunistic behavior or abuse [8,33]. Many studies suggested incorporating incentives into the contract (e.g., revenue sharing) to facilitate the implementation of joint sustainability initiatives [12,37].…”
Section: Effects Of Contractual Governancementioning
confidence: 99%
“…Many studies have empirically verified the benefits of supply chain information sharing, including shortening lead time, improving forecasting, mitigating the bullwhip effect, and reducing inventory [8,30]. In the case of sustainability collaboration, Lin and Chen [39] found that sharing production plan and shipment information with their 3PL providers would significantly improve after-sale service.…”
Section: Effects Of Relational Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Technical eco-innovations take place in products and processes and involve technologies aimed at improving the environmental performance of products and processes. Non-technical eco-innovations include people-oriented changes which normally occur in marketing (related to implementation of more green product design and packaging, pricing, distribution and promotion activities) ( [33]), organizational (shift to a new or improved ecological-oriented managerial arrangement such as Environmental Management System (EMS)) ( [34]), institutional (includes improvement of values, norms, culture and behaviour) ([1]) and system (systemic level transformation among networked organizations which involve combination of all other types of eco-innovation -product, process, marketing, organizational and institutional) ( [35]). The concern of this study is on the technological eco-innovation which taking place in the production processes.…”
Section: Definition and Nature Of Eco-innovationmentioning
confidence: 99%
“…The concern of this study is on the technological eco-innovation which taking place in the production processes. [34] and [12] used the term "eco-process innovation" to describe this type of eco-innovation, and the similar term is also used throughout the discussion of this paper.…”
Section: Definition and Nature Of Eco-innovationmentioning
confidence: 99%